Meningkatkan Kemampuan Menyimak melalui Metode Bercerita pada Anak Usia Dini - Prasiwi, Agni Ayu (Universitas Muhammadiyah Magelang, 2018)
The study aims to improve the listening ability through the method of telling the story of the children of group A TK Pertiwi Rejowinangun Selatan Magelang City. Research is a classroom action research consisting of four stages: planning, implementation, observation and reflection. The research was conducted in TK Pertiwi Rejowinangun Selatan Kota Magelang. The subjects of this study are students of Group A of TK Pertiwi Rejowinangun Selatan Kota Magelang, amounting to 12 children. Variables used in the study include input variables (listening ability before action), process variables (storytelling method) and output variables (listening ability after action). Methods of data collection using observation method. Methods of data analysis using descriptive statistical analysis percentage, with success indicator> 75%. The conclusion of the research result proves that storytelling is effective to improve the listening ability in group A TK Pertiwi Rejowinangun Selatan Magelang City. The result of preliminary observation is known that average listening ability only reach 60,9%. After the learning activities using the storytelling method, the average achievement of listening ability of subjects increased to 86.1%, has exceeded the target set that is> 75%.